2010
DOI: 10.1007/s00535-010-0288-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of desmoplastic reaction in biopsy specimens is useful for predicting the depth of invasion of early colorectal cancer: a Japanese collaborative study

Abstract: Detection of DR in pretreatment biopsy specimens is useful for the prediction of SM depth in nonpedunculated SICRCs, and may be useful for the selection of such cases that would be treatable by endoscopic mucosal resection and endoscopic submucosal dissection (EMR/ESD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…In the multicenter collaborative studies led by the Japanese Society for Cancer of the Colon and Rectum (JSCCR) [1,6], we previously demonstrated that the biopsy specimens from Group B were frequently evaluated as DR-positive lesions. These pathological examinations were performed on sections stained with H & E. Thus, these studies revealed that it is possible to predict SM depth by diagnosis of pretreatment biopsy specimens, especially in non-pedunculated, but not in pedunculated CRCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the multicenter collaborative studies led by the Japanese Society for Cancer of the Colon and Rectum (JSCCR) [1,6], we previously demonstrated that the biopsy specimens from Group B were frequently evaluated as DR-positive lesions. These pathological examinations were performed on sections stained with H & E. Thus, these studies revealed that it is possible to predict SM depth by diagnosis of pretreatment biopsy specimens, especially in non-pedunculated, but not in pedunculated CRCs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, discrimination between M/SM1 CRC (Group A) and SM2 CRC (Group B) is very important for selecting therapeutic modalities against SM CRC. We also previously reported that the detection of desmoplastic reaction (DR) in pretreatment biopsy specimens was useful for predicting the SM depth in non-pedunculated, but not in pedunculated SM CRCs [1,6]. In these studies, DR was evaluated by hematoxylin and eosin (H&E) staining of the biopsy specimens, although it was difficult to diagnose DR in some cases of pedunculated CRCs [1].…”
Section: Introductionmentioning
confidence: 99%
“…A retorospective study for detection of desmoplastic reaction in biopsy specimens of early colorectal cancer reported that 359 patients with SICRCs, who had undergone surgical or endoscopic mucosal resection, were analysed [23]. For pedunculated (Ip type) SICRCs was not significantly related to submucosal depth.…”
Section: Detection Of Desmoplastic Reaction In Biopsy Specimens Of Comentioning
confidence: 99%
“…Detection of DR in pretreatment biopsy specimens is useful for the prediction of submucosal depth in nonpedunculated (non-Ip) SICRCs, Table 7. Relationship between depth of submucosal invasion and DR in biopsy specimens of patients with SICRCsretorospective study -(adapted from [23])…”
Section: Detection Of Desmoplastic Reaction In Biopsy Specimens Of Comentioning
confidence: 99%
“…However, a desmoplastic reaction (DR), characterized by stromal myofibroblast infiltration of the outermost layers of the tumor (8), is considered to be a response to the invasion of carcinoma cells beyond the muscularis mucosae into the submucosa (SM) or deeper layers (9). Detection of a DR may be useful for predicting massive SM invasion by colorectal carcinoma (10).…”
Section: Introductionmentioning
confidence: 99%